Purification and activity determination of ADAMTS-4 and ADAMTS-5 and their domain deleted mutants - Fowkes, MM; Lim, NH (Humana Press, 2019)
AA disintegrin-like and metalloproteinase with thrombospondin type-1 motifs-4 (ADAMTS-4) and ADAMTS-5 are zinc-dependent metalloproteinases that are involved in the maintenance of cartilage extracellular matrix (ECM) and are currently considered the major aggrecanases in the development of osteoarthritis. In this chapter we describe the establishment and cultivation of cell lines expressing ADAMTS-4,-5 and their domain deletion mutants; the collection of medium containing expressed ADAMTS-4,-5; the subsequent purification of this medium through anti-FLAG affinity chromatography; and the characterization of ADAMTS-4,-5 activity using synthetic Förster resonance energy transfer (FRET) peptide substrates.